PERAN BUDAYA SEKOLAH DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK KELAS V SD INPRES MONCONGLOE KABUPATEN GOWA - Nurannisa; Martini; Hasan, Salim; Muhammad Syahrul; Muh. Aidil Sudarmono R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of school culture in shaping the character of fifth-grade students at SD Inpres Moncongloe, Gowa Regency, and to identify the obstacles in its implementation. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the principal, teachers, students, and parents. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that school culture plays an important role in character building through the habituation of positive values, teacher role modeling, and the consistent implementation of school norms and traditions. The character values developed include religiosity, discipline, responsibility, nationalism, and social awareness. However, several obstacles were identified, such as inconsistent implementation of school culture, differences in teachers’ understanding, limited time management, diverse student backgrounds, and limited parental involvement. Overall, school culture is an effective strategy for supporting character development when implemented consistently and supported by all members of the school community and families.